1996
DOI: 10.1097/00006676-199610000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Morphometric and Biochemical Study on Pancreatic Amylase in Normal and Streptozotocin-Diabetic Rats

Abstract: The number, volume, and size of zymogen granules in pancreatic acinar cells of normal and streptozotocin-diabetic rats were measured using stereological techniques. These morphometric data were then correlated with the amylase activity of the acinar cells. In the normal rats, the acinar cells had a mean volume of 1,253.5 Km' and contained 343 zymogen granules, which occupied a volume of 103 pm' of the cell (8.28%). In the diabetic rats, the mean acinar cell volume was estimated as 1,017 km3 and the cell contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
3
7
0
Order By: Relevance
“…The β-cell volume for freshly isolated islets reflects an estimated 5% loss from the commonly accepted value of about 1,000 μm 3 for the native pancreas (32, 33), which is consistent with a partial degranulation during isolation and dispersion. Acinar volume in the mature pancreas on average is within the 1,300 to 1,800 μm 3 range reported for the adult rat (34-36) and it is assumed that about 20 to 25% of the volume in freshly isolated preparations is lost from degranulation. Estimates for duct and other cells are from our observations (Bonner-Weir, S., unpublished).…”
Section: Number Fraction and Volume Fraction Relationships In Islet Pmentioning
confidence: 74%
“…The β-cell volume for freshly isolated islets reflects an estimated 5% loss from the commonly accepted value of about 1,000 μm 3 for the native pancreas (32, 33), which is consistent with a partial degranulation during isolation and dispersion. Acinar volume in the mature pancreas on average is within the 1,300 to 1,800 μm 3 range reported for the adult rat (34-36) and it is assumed that about 20 to 25% of the volume in freshly isolated preparations is lost from degranulation. Estimates for duct and other cells are from our observations (Bonner-Weir, S., unpublished).…”
Section: Number Fraction and Volume Fraction Relationships In Islet Pmentioning
confidence: 74%
“…28) In the present study, 40 mg/kg of STZ markedly decreased serum and pancreatic amylase activities, thus agreeing with these previous studies. [22][23][24] However, HJ administration did not markedly change serum amylase activity, and serum amylase activity for the STZϩHJ group was significantly lower throughout the study period when compared to the control group except for the second week. Pancreatic amylase activity for the STZϩHJ group was also significantly higher when compared to the STZ group but significantly lower when compared to the control group, thus clarifying that HJ did not normalize serum and pancreatic amylase activities.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have investigated the changes in pancreatic secretion function using STZ-induced diabetes models, [21][22][23][24][25] and all found that amylase activity was significantly decreased in STZ-treated rats. Moreover, some studies documented that insulin stimulated the transcription and translation of amylase mRNA, 26,27) and it is therefore likely that insulin stimulates amylase secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the changes in pancreatic secretion function using STZ-induced diabetes models, (Duanet al, 1989;Aughsteen et al, 1996;Anderson and Bevan, 1992;Yoshihiko et al, 2007) and all found that amylase activity was significantly decreased in STZ-treated rats. Moreover, some studies documented that insulin stimulated the transcription and translation of amylase mRNA and it is therefore likely that insulin stimulates amylase secretion (Patel et al,2004).…”
Section: (E) Total Antioxidant Capacity (D) Triglyceridementioning
confidence: 99%